Expenditure on research and development and its impact on some macroeconomic variables: Iraq is a case study for the period 1990-2018 - Qader, Kulthum; Zahir, Abdulhameed (Humanities Journal of University of Zakho, 2022)
The aims of the research is to measure the impact that spending on research and development activity on the growth of some macroeconomic variables during the period (1990-2018). A number of conclusions have been reached, including: that there is an inverse relationship significant between expenditure on research and development and expenditure size on higher education, while the relationship was positive and significant between the expenditure variable on research and development and each of (unemployment rate, per capita share of GDP, Total capital formation, and the value of non-oil commodity exports) during the period covered by the study. In light of the conclusions reached, a number of proposals were presented, including: the necessity of increasing the amounts allocated for research and development purposes directed to applied scientific research in order to achieve the maximum possible benefit from the scientific cadres in the country, encouraging the private sector to contribute to funding research and development activities. ، البطالة، الصادرات السلعية، تصحيح الخطأ، نموذج ARDL).